Per la storia antica dell’Antologia Salmasiana - MONDIN, Luca; CRISTANTE, Lucio (AL. Rivista di studi di Anthologia Latina, 2010)
Abstract In spite of the losses and many accidents in the text’s transmission, the first part of Codex Salmasianus (Par. Lat. 10318) keeps accurately enough on the structure and the original content of an extensive poetic miscellany, assembled in Chartage immediately after the Vandalic domination (533-534). A new structural examination of the so-called ‘Salmasian Anthology’ has recognized the signs of an unitary project, which certainly goes back to the work of a single editor. Moreover, the emendation of a textual corruption at the beginning of the enigmatic Praefatio (AL 19 R.2 = 6 Sh.B.) has allowed to identify Luxorius not only as the leading poet of the anthology but also as the author of the Praefatio itself, and the editor of the whole collection. The Praefatio, whose obscure language is a real code of initiation, shows that the anthology is not an individual but collective work, born within a society of Chartaginian docti uiri. They concur to the creation of the corpus with their own poems, their review, and also with their grammatical knowledge especially as regards the correct prosody.